Identification and Characterization of bZIP Gene Family Combined Transcriptome Analysis Revealed Their Functional Roles on Abiotic Stress and Anthocyanin Biosynthesis in Mulberry (Morus alba) - Qinghua Liu; Haowen Fang; Hong Zhou; Xiling Wang; Zhiwei Hou (Horticulturae)
The basic leucine zipper (bZIP) gene family constitutes one of the most abundant and conserved transcription factor families in plants, which participates in diverse physiological processes including response to abiotic stress, anthocyanin accumulation, and the regulation of plant growth and development. Although bZIP genes play an important role in plants, comparable studies in mulberry are lacking, particularly regarding their response under abiotic stress conditions. In this study, we identified 56 mulberry bZIP transcription factors and divided these members into 12 groups by phylogenetic analysis. The coding genes of these bZIPs harbor a large number of segmental duplications and are unevenly distributed on 12 chromosomes. We further identified numerous stress responsive elements in the promoter regions of bZIP genes. Furthermore, by analysis of the expression profiles from RNA-seq data, we identified MabZIP43 and MabZIP24 that respond to heat, salt–alkaline, and high light stress. We also found that the gene expression of MabZIP16 was closely related to anthocyanin biosynthesis. As described, we systematically explored the structures and functions of the bZIP gene family in Morus alba. The results imply that the bZIP gene family plays significant roles in stress response and anthocyanin biosynthesis. Three bZIP candidate genes are suggested for genetic engineering to improve the resistance of mulberry to stress and for high-anthocyanin-producing lines.